Reflection of feminism in the arts of modern Kazakhstani painters (Journal of Philosophy Culture and Political Science, 2021)
The article touches on the topic of self-expression of contemporary artists through their work concerning feminism. The theme of the woman, her inner world, and the attitude towards her in different historical epochs have always occupied a special place in the visual arts. There is hardly an artist who does not understand this mystery, but everyone has discovered it in their way. The progress of civilization gradually awakened the consciousness of women. People are beginning to realize that women occupy an important place in the humanities, the arts, and other fields. The emergence of feminism has led to profound social changes in the world. The emergence of feminist works in art history is an objection to the once-dominant artistic paradigm and enriches the traditional art genre.The concept of modern art feminism emerged due to the formation and development of modern civil society and public space. It is a form of contemporary art expression in a public space and an artistic medium for communication between people and the environment.The definition of feminism is the simplest one. It's the idea that a work of art could portray women's power, independence, quality, dignity, and identity.Keywords: art, feminism, artist, the modern art of Kazakhstan